Detection of Molecular Diversity in Bacillus atrophaeus by Amplified Fragment Length Polymorphism Analysis - Burke, S. A. (American Society for Microbiology, 2004)
Phenotypically, Bacillus atrophaeus is indistinguishable from the type strain of Bacillus subtilis except by virtue of pigment production on certain media. Several pigmented variants of B. subtilis have been reclassified as B. atrophaeus, but several remain ambiguous in regard to their taxonomic placement. In this study, we examined strains within the American Type Culture Collection originally deposited as Bacillus globigii, B. subtilis var. niger, or Bacillus niger using 16S rRNA gene sequencing and amplified fragment length polymorphism (AFLP) analysis to determine the level of molecular diversity among these strains and their relationship with closely related taxa. The 16S rRNA gene sequences revealed little variation with one base substitution between the B. atrophaeus type strain ATCC 49337 and the other pigmented bacilli. AFLP analysis produced high-quality DNA fingerprints with sufficient polymorphism to reveal strain-level variation. Cluster analysis of Dice similarity coefficients revealed that three strains, ATCC 31028, ATCC 49760, and ATCC 49822, are much more closely related to B. atrophaeus than to B. subtilis and should be reclassified as B. atrophaeus. A very closely related cluster of B. atrophaeus strains was also observed; this cluster was genetically distinct from the type strain. The level of variation between the two groups was approximately the same as the level of variation observed between members of the two B. subtilis subspecies, subtilis and spizizenii. It is proposed that the cluster of strains typified by ATCC 9372 be designated a new subspecies, B. atrophaeus subsp. globigii.